Design Refinement of Catalytic System for Scale-Up Mild Nitrogen Photo-Fixation - Wang, Xiao Hu; Wu, Bin; Zhu, Yongfa; Wang, Dingsheng; Li, Nian Bing; Xu, Zhichuan J.; Luo, Hong Qun (Nano-Micro Letters, 2025)
Ammonia and nitric acid, versatile industrial feedstocks, and burgeoning clean energy vectors hold immense promise for sustainable development. However, Haber–Bosch and Ostwald processes, which generates carbon dioxide as massive by-product, contribute to greenhouse effects and pose environmental challenges. Thus, the pursuit of nitrogen fixation through carbon–neutral pathways under benign conditions is a frontier of scientific topics, with the harnessing of solar energy emerging as an enticing and viable option. This review delves into the refinement strategies for scale-up mild photocatalytic nitrogen fixation, fields ripe with potential for innovation. The narrative is centered on enhancing the intrinsic capabilities of catalysts to surmount current efficiency barriers. Key focus areas include the in-depth exploration of fundamental mechanisms underpinning photocatalytic procedures, rational element selection, and functional planning, state-of-the-art experimental protocols for understanding photo-fixation processes, valid photocatalytic activity evaluation, and the rational design of catalysts. Furthermore, the review offers a suite of forward-looking recommendations aimed at propelling the advancement of mild nitrogen photo-fixation. It scrutinizes the existing challenges and prospects within this burgeoning domain, aspiring to equip researchers with insightful perspectives that can catalyze the evolution of cutting-edge nitrogen fixation methodologies and steer the development of next-generation photocatalytic systems. Highlights: 1 The review provides a brief overview of basic mechanisms, element selections, activity confirmation, and experimental protocols of photocatalytic nitrogen fixation under mild conditions. 2 The review details strategies for scale-up photocatalysts in nitrogen fixation, emphasizing defect engineering, facet optimization, heteroatom doping, single-atom site creation, and composite synthesis. 3 The review emphasizes the importance of environmental assessment for photocatalyst lifecycle sustainability in mild nitrogen fixation for the future.